Peran Guru dalam Pembentukan Etika dan Moral Siswa: Perspektif Pendidikan Modern - Alya Rachma; Tifany Laura Balqis; Ameliya Harahap (Pusat Riset dan Inovasi Nasional, 2024)
The formation of students' ethics and morals is one of the crucial aspects of education, aiming not only to enhance academic knowledge but also to shape good character. In a continuously changing and challenging social context, the need for education that instills moral and ethical values becomes increasingly urgent. This aligns with the role of education. Although there have been many studies discussing the importance of character education, there is still a gap in understanding the specific role of teachers in this context. This research utilizes a qualitative method with a literature review approach.